Student Passengers’ Assessment On The Transsarbagita Bus Service Quality - Wedagama, D.M Priyantha (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2015)
This study aims to investigate the impact of tangible, reliability, responsiveness, assurance, and empathy factors of TransSarbagita bus services based on student passengers’ perceptions and expectations. Two synthetic indices of CSI and HCSI are determined to identify influencing attributes on bus quality service. Both indices produce the same percentages of 32.7% showing low student passengers’ satisfactions. Quadrant Analysis suggests TransSarbagita bus services should be more concentrated on improving their punctual operations. This is urgently required to keep the existing customers and to attract more new passengers in particular, those students who may be shifted from motorcycle. The local government is highly recommended to accelerate the implementation of the bus network for the Sarbagita regions.